NON-VERBAL SIGNS OF POTENTIALLY DANGEROUS AIR PASSENGERS - L. G. Shumkova; I. V. Kuznetsova; V. M. Ilyin (Научный вестник МГТУ ГА)
The paper deals with problem of air passengers’ non-verbal signs identification while ensuring aviation security. The danger is not only the passengers intentionally preparing acts of unlawful interference in civil aviation, but also unbalanced passengers with increased anxiety. The non-verbal signs of both passenger categories are frequently identical. Safety control on the ground and in the air depends on the timely transfer in information about potentially dangerous passengers from aviation security profilers to flight attendants.